Pengaruh Pemasaran Jasa Terhadap Kepuasan Pelanggan Dalam Memilih Produk Jasa Di Kantor PT. Pegadaian (Persero) Cabang Medan Mandala - Natalia E Sihombing (Jurnal Ilmu Sosial Dan Politik, 2022)
This study aims to analyze the effect of service marketing namely Product, People, and Process on Customer Satisfaction in choosing products at PT. Pegadaian (Persero) Medan Mandala branch. This research is a survey research. The sample is 120 people with data collection using a questionnaire. The technique of determining the sample is purposive sampling. Testing the basic assumptions of the research used is the validity test and the reliability test, the classical assumption. Hypothesis testing used partial significant test, simultaneous significant test, and coefficient of determination (R2). The results showed that there was an effect of Product, People, and Process partially or simultaneously on customer satisfaction in choosing a product. The R value is 0.728 (72.8%), indicating that the level of relationship between the independent variables is strongly related. And the value of R Square shows 0.53 or 53%, which means 53% customer satisfaction in choosing products at PT. Pegadaian (Persero) Medan Mandala branch can be explained by the variables Product, People, and Process while the remaining 47%, influenced by other factors not examined in this study.